Mechanisms for enforcing the obligations contained in the some treaties to combat terrorism (قضايا سياسية, 2024)
Research Summary: The issue of combating terrorism is one of the goals that countries around the world seek to achieve through various means, given the magnitude of the challenge that this phenomenon represents at all levels - security, political, intellectual, economic, legal...etc. As a result of the above, interest has emerged in combating terrorism by concluding a group of international agreements since the existence of the League of Nations, where a treaty was concluded in 1937, which did not enter into force because a sufficient number of countries did not ratify it. After the establishment of the United Nations in 1945, a treaty was concluded. A group of international agreements that aimed to create an agreement framework to combat specific forms of terrorism included mechanisms to ensure the implementation of the obligations established or adopted by these agreements. However, it is noted that there is a clear difference between the mechanisms adopted by each agreement compared to other agreements at a time when modern forms emerge. For terrorism, such as cyberterrorism, biological terrorism, etc Thus, we go beyond the stage of forms of terrorism in its traditional or known historical forms, as terrorism is an ancient phenomenon, which requires activating the agreements to combat this dangerous phenomenon that threatens the security of humanity and international peace and security by developing mechanisms for compliance with the obligations established by these agreements, so that we move to the stage of ensuring compliance by creating... Mechanisms of an advanced institutional nature, which is the mechanism resorted to by the Shanghai Agreement concluded in 2001 relating to combating terrorism, extremism and separatist movements when it established a body called the “Center for Regional States Parties to Combat Terrorism in accordance with Article 10”. Among them, while we did not find any resort to such a mechanism in other agreements related to combating various forms of terrorism, as the enforcement mechanisms were limited to emphasizing the necessity of adhering to the aforementioned agreements in application of general and basic legal principles without finding means of compliance of an institutional nature, as these general legal principles were represented The basic principles are the principle of Good Faith, the principle of fulfillment of the covenant (pacta sunt servant), and the general commitment to solidarity. And implementing the principle of cooperation and mutual assistance, implementing the principle of the obligation to extradite or prosecute, taking legislative measures, creating judicial jurisdiction, implementing the principle of reporting and resorting to investigation, and negotiating and arbitration mechanisms, as well as resorting to the International Court of Justice to settle any disputes related to the agreements related to combating terrorism, as well as The Arab Convention to Combat Terrorism concluded in 1998 created media and educational mechanisms that we did not find parallels in most other agreements.